Rekayasa dan Penguatan Lembaga Menghadapi Persaingan Global Berbasis Wirausaha dan Etika Islam - Deden Gandana Madjakusumah; Udin Saripudin; Suryani Suryani (El Barka, 2020)
Abstract: The economic trends of countries in the world tend to lead to globalization and several countries that have a common interest in forming a global place in a narrower or regional scope such as AFTA, APEC, NAFTA, and so on are the efforts of countries that are members of these organizations. to be able to compete in the global economy. This paper aims to elaborate the concept of engineering and strengthening of entrepreneurial institutions and Islamic ethics in order to face the era of the global market. This study uses the literature study method, namely by studying various sources and literature related to institutional strengthening, entrepreneurship, and Islamic ethics. The results of the study concluded that organizational development as an engineering and strengthening of institutions to improve global competitiveness based on entrepreneurship and Islamic ethics can be an alternative solution for government, private and community institutions in facing competition between institutions that demand that each institution can have a competitive advantage and make values entrepreneurship and Islamic ethics as a basis in Engineering and Strengthening Institutions to enhance global competitiveness.